Perceptions, social life, treatment and education gap of Tanzanian children with epilepsy: A community-based study - Mushi, D; Burton, K; Mtuya, C; Gona, J; Walker, R; Newton, C (2012)
The effects of epilepsy on children and their families, factors influencing the treatment and education gap and socio-cultural beliefs about epilepsy in children in rural sub-Saharan Africa are not clearly defined.We conducted a qualitative study, with 38 in-depth interviews and 2 focus group discussions with carers of children with epilepsy (CWE) in Tanzania.Discrimination, isolation and lack of hope were identified as major issues. Poor school attendance was attributed to learning difficulties, behavior problems, ongoing seizures and restricted school access. The treatment gap was related to misdiagnosis, preferential use of traditional treatment and cost of biomedical treatment. The hopes expressed for the future centered on access to treatment and education.Improved access to diagnosis, cost-effective treatment, sensitization of the community on epilepsy, collaborative care provision with traditional and faith healers and improved access to specialist schooling could improve the quality of life and future of CWE in this region. © 2012 Elsevier Inc.